2017
DOI: 10.1080/13557858.2017.1373075
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes fatalism and its emotional distress subscale are independent predictors of glycemic control among Lebanese patients with type 2 diabetes

Abstract: This is the first study in the Arab region that identifies diabetes fatalism as an independent predictor of glycemic control among Lebanese. Future studies should further investigate this construct to guide interventions that can address it for better diabetes outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Although targeted by our education program, diabetes fatalism and its 3 subscales (despair, hopelessness, and powerlessness) (Egede & Ellis, 2010) did not change from baseline, which might indicate that fatalism in this population is a constant trait (as opposed to a state like depression), a culturally grounded belief that is non-modi able by such intervention. We have previously demonstrated in a larger scale study that diabetes fatalism is widespread in Lebanon and is associated with poor glycemic control (Sukkarieh-Haraty, Egede, Abi Kharma, & Bassil, 2017, 2018. Thus, as a clinical implication, diabetes fatalism can be assessed as an additional nonmodi able risk factor for poor diabetes outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although targeted by our education program, diabetes fatalism and its 3 subscales (despair, hopelessness, and powerlessness) (Egede & Ellis, 2010) did not change from baseline, which might indicate that fatalism in this population is a constant trait (as opposed to a state like depression), a culturally grounded belief that is non-modi able by such intervention. We have previously demonstrated in a larger scale study that diabetes fatalism is widespread in Lebanon and is associated with poor glycemic control (Sukkarieh-Haraty, Egede, Abi Kharma, & Bassil, 2017, 2018. Thus, as a clinical implication, diabetes fatalism can be assessed as an additional nonmodi able risk factor for poor diabetes outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes fatalism did not change from baseline, which might indicate that fatalism in this population is a constant trait (as opposed to a state like depression), a culturally grounded belief that is non-modifiable by a single intervention [ 5 ]. Diabetes fatalism is widespread in Lebanon and is associated with poor glycemic control [ 10 , 11 ]. Alternatively, involving religious authorities in the education program, may ameliorate fatalism more effectively since it is closely related to religious beliefs among Arabs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…glycemic levels [10,11]. Lebanese patients T2DM demonstrated low levels of physical exercise [12] and the majority do not receive complete therapeutic management recommended for patients on chronic medication [13].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified fatalistic beliefs that emanated from illness and health beliefs and affected diabetes outcomes. Sukkarieh‐Haraty et al (2019) revealed that diabetes fatalism and emotional distress were significantly associated with high HbA1c while diabetes education, advanced age and female gender had a positive impact on HbA1c. Similarly, San Diego et al (2020), explored the interaction of diabetes knowledge and health fatalism as predictors of type 2 diabetes preventive behaviour.…”
Section: Discussionmentioning
confidence: 99%